Dental Office Prevention of Coronavirus Infection - D’Amico, Cesare; Bocchieri, Salvatore; Stefano, Rosa De; Gorassini, Francesca; Surace, Giovanni; Amoroso, Giulia; Scoglio, Cristina; Mastroieni, Roberta; Gambino, Dario; Amantia, Emanuele Mario; Marino, Stefania; Stumpo, Chiara; Fiorillo, Luca (European Journal of Dentistry, 2020)
Coronavirus disease is now spreading in different countries of the world. The alarmism created through the media also creates confusion in people about virus spreading. The health care environments among which the dental practice could be places of spread of the virus, especially places where patients with systemic pathology could be exposed to this. The purpose of this article is to clarify coronavirus disease 2019 and its management in the dental practice. Only by following the normal guidelines on disinfection and sterilization of environments and operators, with some additional rules on the management of patients in the waiting room, it is possible to limit this risk. Limiting the risk of spreading the virus is one of the keys to its eradication.
Keywords: coronavirus disease 2019; infection risk; public health; dental office; virus